The Potential of Local Food as a Solution to National Nutrition Security in the Midst of the Threat of a Global Food Crisis - Tasya, Amalia (Journal Nutrizione, 2025)
Nutritional intervention in the first 1,000 days of life (HPK) is an important strategy to prevent stunting and improve the quality of child growth. This study aims to evaluate the effectiveness of nutrition intervention programs in Indonesia and identify challenges in their implementation. The method used was a qualitative study with a case study approach, involving 30 informants consisting of health workers, program managers, and mothers of toddlers from urban, rural, and 3T (Frontier, Outermost, Disadvantaged) areas. Data was collected through in-depth interviews and analysis of official documents, then analyzed thematically to identify the success factors and constraints of the program. The results showed that local food-based complementary feeding of BREAST MILK (MP-ASI), micronutrient supplementation, and nutrition education contributed significantly to improving children's nutritional status, with maternal adherence highest in urban areas (78%) and lowest in 3T areas (48%). The effectiveness of the intervention was influenced by access to nutritious food, the availability of health workers, the frequency of education, and community participation. This research emphasizes the need for multi-sectoral strategies involving governments, communities, and non-governmental institutions to improve the coverage and quality of nutrition programs, particularly in areas with limited access. The integration of education, food distribution, and community involvement is the key to the success of the intervention in 1,000 HPK.